2005
DOI: 10.1002/ijc.21221
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Com‐1/P8 in human breast cancer and its relevance to clinical outcome and ER status

Abstract: Com‐1 is a recently discovered molecule that has putative action on the metastatic nature of cancer cells. The molecular action and clinical implication in cancer and prognosis are yet to be established. The current study examined the role of Com‐1 in a cohort of patients with breast cancer, with particular emphasis on its relationship with clinical outcomes and ER status. A panel of human breast cancer cell lines were tested. A cohort of breast cancer tumours (n‐120) with matched normal non‐neoplastic mammary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…In particular, a large number of upregulated genes were involved in the modulation of immunological functions, suggesting that the accumulation in the hepatocytes of viral proteins yielded cellular damage followed by an immune response (23,27,29). In addition, several upregulated transcripts have already been correlated to cellular dysplasia and tumor malignancy in different types of cancer (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). The microarray data showed the upregulation of NuprI, a transcription factor whose overexpression is inversely correlated with apoptosis in pancreatic cancer (60), and the downregulation of the proapoptotic gene Bnip3 (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, a large number of upregulated genes were involved in the modulation of immunological functions, suggesting that the accumulation in the hepatocytes of viral proteins yielded cellular damage followed by an immune response (23,27,29). In addition, several upregulated transcripts have already been correlated to cellular dysplasia and tumor malignancy in different types of cancer (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). The microarray data showed the upregulation of NuprI, a transcription factor whose overexpression is inversely correlated with apoptosis in pancreatic cancer (60), and the downregulation of the proapoptotic gene Bnip3 (61,62).…”
Section: Discussionmentioning
confidence: 99%
“…The Q-PCR used was the Amplifluor™ Uniprimer™ system (Intergen Company Oxford, UK) and the Thermo-Start ® (ABgene, Epsom, Surrey, UK), as previously reported (12,13). Specific primers were designed by the authors using Beacon Designers software (Biosoft, Palo Alto, CA, USA) and manufacturated by Invitrogen (Invitrogen Life Technologies, Paisley, UK).…”
Section: Real-time Quantitative Polymerase Chain Reaction (Q-pcr)mentioning
confidence: 99%
“…Sections were counterstained in Gill's haematoxylin and dehydrated in ascending grades of methanol before clearing in xylene and mounting under a cover slip. Semi-quantification of staining intensity was carried out using Optimas package as we previously described (13). Immunohistochemical photographs of normal and tumour sections (n=20) were assessed as previously described (15).…”
Section: Real-time Quantitative Polymerase Chain Reaction (Q-pcr)mentioning
confidence: 99%
“…whether it is stimulating or inhibiting may vary in different malignancies. COM1 has been found to aid the establishment of metastasis and to play a key role in the progression of malignancies of breast (1,(5)(6)(7)13), thyroid (4,13,14), central nervous system (15) and pancreas (3,16,17). COM1 has been implicated in inducing chemoresistance in pancreatic and breast cancer cells, protecting them from apoptosis and making tumour cells genetically unstable (17).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer cells have markedly reduced nuclear distribution of the COM1 protein compared with normal mammary epithelial cells. Low levels of COM1 were associated with nodal status and poor clinical outcome (5). A follow-up study showed that the nuclear presence of the COM1 protein was crucial to its inhibitory role in cancer cells, and that loss of its nuclear presence of this molecule had a detrimental effect on its overall negative control of cancer growth (6).…”
Section: Candidate Of Metastasis 1 Regulates In Vitro Growth and Invamentioning
confidence: 99%